Repression of PFKFB3 sensitizes ovarian cancer to PARP inhibitors by impairing homologous recombination repair - Yinan Xiao; Yu Wu; Qilong Wang; Mo Li; Chaolin Deng; Xiaoyang Gu (Cell Communication and Signaling)
Abstract Background Ovarian cancer (OC), particularly high-grade serous ovarian carcinoma (HGSOC), is the leading cause of mortality from gynecological malignancies worldwide. Despite the initial effectiveness of treatment, acquired resistance to poly(ADP-ribose) polymerase inhibitors (PARPis) represents a major challenge for the clinical management of HGSOC, highlighting the necessity for the development of novel therapeutic strategies. This study investigated the role of 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase 3 (PFKFB3), a pivotal regulator of glycolysis, in PARPi resistance and explored its potential as a therapeutic target to overcome PARPi resistance. Methods We conducted in vitro and in vivo experiments to assess the role of PFKFB3 in OC and its impact on PARPi resistance. We analyzed PFKFB3 expression and activity in primary OC tissues and cell lines using western blotting and immunohistochemistry. CRISPR-Cas9 and pharmacological inhibitors were employed to inhibit PFKFB3, and the effects on PARPi resistance, homologous recombination (HR) repair efficiency, and DNA damage were evaluated. RNA sequencing and proximity labeling were employed to identify the molecular mechanisms underlying PFKFB3-mediated resistance. The in vivo efficacy of PARPi and PFK158 combination therapy was evaluated in OC xenograft models. Results PFKFB3 activity was significantly elevated in OC tissues and associated with PARPi resistance. Inhibition of PFKFB3, both genetically and pharmacologically, sensitized OC cells to PARPis, impaired HR repair and increased DNA damage. Proximity labeling revealed replication protein A3 (RPA3) as a novel PFKFB3-binding protein involved in HR repair. In vivo, the combination of PFK158 and olaparib significantly inhibited tumor growth, increased DNA damage, and induced apoptosis in OC xenografts without exacerbating adverse effects. Conclusions Our findings demonstrate that PFKFB3 is crucial for PARPi resistance in OC. Inhibiting PFKFB3 sensitizes HR-proficient OC cells to PARPis by impairing HR repair, leading to increased DNA damage and apoptosis. PFKFB3 represents a promising therapeutic target for overcoming PARPi resistance and improving outcomes in OC patients.